FLCN-regulated miRNAs suppressed reparative response in cells and pulmonary lesions of Birt-Hogg-Dubé syndrome. Issue 6 (17th March 2020) - Min, Haiyan; Ma, Dehua; Zou, Wei; Wu, Yongzheng; Ding, Yibing; Zhu, Chengchu; Lin, Anqi; Song, Shiyu; Liang, Qiao; Chen, Baofu; Zhang, Bin; Wan, Yueming; et al.
Abstract : Background: Birt-Hogg-Dubé Syndrome (BHDS) characterised by skin fibrofolliculomas, kidney tumour and pulmonary cysts/pneumothorax is caused by folliculin (FLCN) germline mutations. The pathology of both neoplasia and focused tissue loss of BHDS strongly features tissue-specific behaviour of the gene. Isolated cysts/pneumothorax is the most frequent atypical presentation of BHDS and often misdiagnosed as primary spontaneous pneumothorax (PSP). Deferential diagnosis of BHDS with isolated pulmonary presentation (PSP-BHD) from PSP is essential in lifelong surveillance for developing renal cell carcinoma. Methods: The expression profiles of microRNAs (miRNAs) in cystic lesions of PSP-BHD and PSP were determined via microarray. The selected upregulated miRNAs were further confirmed in the plasma of an expanded cohort of PSP-BHD patients by reverse transcription quantitative PCR (RT-qPCR). Their diagnostic accuracy was evaluated. Moreover, the cellular functions and targeted signalling pathways of FLCN-regulated miRNAs were assessed in various cell lines and in the lesion tissue contexts. Results: Cystic lesions of PSP-BHD and PSP showed different miRNAs profiles with a significant upregulation of miR-424–5p and let-7d-5p in PSP-BHD. The combination of the two effectively predicted BHDS patients. In vitro studies revealed a suppressive effect of FLCN on miR-424–5p and let-7d-5p expressions specifically in lung epithelial cells. The ectopic miRNAs triggered epithelial apoptosis and epithelial transition of mesenchymal cells and suppressed the reparative responses in cells and tissues with FLCN deficiency. Conclusion: The upregulation of miR-424–5p and let-7d-5p by FLCN deficiency occurred in epithelial cells and marked the PSP-BHD condition, which contributed to a focused degenerative pathology in the lung of PSP-BHD patients.